Sexual violence against Yazidi women by ISIS members and how they are prosecuted internationally Analytical legal research - جلال, گەشە دارا جلال; خضر, آ.م.د. شوان عمر خضر (Sulaimani Journal for Humanities, 2025)
This study investigates the sexual crimes committed by ISIS against Yazidi women and the possibility of bringing these offenses up for trial before the International Criminal Court. It also investigates their legal classification as international crimes, such as crimes against humanity, genocide and war crimes. The study analyzes and nging these offenses up for trial before the International Criminal Court, especially given Iraq's non-signatory status on the Rome Statute, which limits the International Criminal Court jurisdiction. It also highlights the challenges of Iraq's lack of cooperation with the International Criminal Court. Additionally, in addition to examining the jurisdiction of the International Criminal Court, the study study alternative legal mechanisms, including special or hybrid courts, as a more practical and efficient route to justice. These alternatives are crucial in addressing the limitations that the international justice system poses in the prosecution of crimes of sexual violence during armed conflicts. By emphasizing prosecution of these crimes, the study underscores the importance of holding perpetrators accountable and strengthening international legal norms against such violations. Addressing sexual violence in conflict not only seeks justice for victims but also strengthens efforts to combat these heinous crimes, ensuring they are met with the severity they deserve. This approach fosters a more holistic framework for international justice.